2017
DOI: 10.1155/2017/5798372
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alexithymia, Anxiety, and Depression in Predicting Self-Efficacy in Academic Students

Abstract: Objective. Little research is available on the predictive factors of self-efficacy in college students. The aim of the present study is to examine the role of alexithymia, anxiety, and depression in predicting self-efficacy in academic students. Design. In a cross-sectional study, a total of 133 students at Babol University of Medical Sciences (Medicine, Dentistry, and Paramedicine) participated in the study between 2014 and 2015. All participants completed the Toronto Alexithymia Scale (TAS-20), College Acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 35 publications
4
30
1
3
Order By: Relevance
“…In this study, the Cronbach's α for the whole scale was .85. This tool has been used with Saudi Arabian mothers and with Iranian university students Depression, Anxiety, and Stress Scale's (DASS‐21) Arabic version was used to measure depression (D), anxiety (A), and stress (S).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the Cronbach's α for the whole scale was .85. This tool has been used with Saudi Arabian mothers and with Iranian university students Depression, Anxiety, and Stress Scale's (DASS‐21) Arabic version was used to measure depression (D), anxiety (A), and stress (S).…”
Section: Methodsmentioning
confidence: 99%
“…Among Egyptian substance abusers, the prevalence of alexithymia was 77% . Among Iranian university students, the prevalence of alexithymia was 21.8% (mean score was 52.79, SD = 9.02) …”
Section: Introductionmentioning
confidence: 95%
“…Moreover, they confirmed that self-efficacy and psychological hardiness have important roles in the educational progression of the students [29]. A study showed that there is significant correlation between psychosocial psychological hardiness and thinking styles [18]. How does psychological hardiness contribute to reducing the amount of psychological distress in events?…”
Section: Discussionmentioning
confidence: 89%
“…9237222). Mental profiles of the students have been reported previously [18]. This paper focuses on critical thinking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation